2007
DOI: 10.1186/1753-6561-1-s1-s146
|View full text |Cite
|
Sign up to set email alerts
|

Two-step intermediate fine mapping with likelihood ratio test statistics: applications to Problems 2 and 3 data of GAW15

Abstract: Construction of precise confidence sets of disease gene locations after initial identification of linked regions can improve the efficiency of the ensuing fine mapping effort. We took the confidence set inference, a framework proposed and implemented using the Mean test statistic (CSI-Mean) and improved the efficiency substantially by using a likelihood ratio test statistic (CSI-MLS). The CSI framework requires knowledge of some disease-model-related parameters. In the absence of prior knowledge of these param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…They have shown that CSI-Mean maintained the desirable statistical properties with this two-step approach. In a recent application of both CSI-MLS and CSI-Mean to the real and simulated data contributed to GAW15 [Sinha and Luo, 2007], we have found that the advantage of CSI-MLS over CSI-Mean is even more pronounced in a two-step CSI procedure, particularly when parental genotypes are not available and when the sample size is large. The reduction in the length of the CI reaches close to 50% in some cases.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…They have shown that CSI-Mean maintained the desirable statistical properties with this two-step approach. In a recent application of both CSI-MLS and CSI-Mean to the real and simulated data contributed to GAW15 [Sinha and Luo, 2007], we have found that the advantage of CSI-MLS over CSI-Mean is even more pronounced in a two-step CSI procedure, particularly when parental genotypes are not available and when the sample size is large. The reduction in the length of the CI reaches close to 50% in some cases.…”
Section: Discussionmentioning
confidence: 96%
“…A comparison of the two procedures in a practical setting where the required parameters are not available has been performed using both the simulated and real data contributed to GAW15 [Sinha and Luo, 2007]. Some results of this comparison will be discussed in the Discussion section.…”
Section: Review Of Confidence Set Inferencementioning
confidence: 98%
See 1 more Smart Citation
“…Thus, careful pre-filtering of data is crucial, not only for reducing multiple testing, but also for censoring outliers likely to give false positives. Sinha and Luo [2007] investigated how ''Intermediate Fine Mapping'' techniques could further refine linkage peaks by improving the precision of confidence sets of disease gene locations, termed confidence set inference (CSI). Sinha and Luo [2007], Lam et al [2007], and Huang et al [2007] concluded incorporating biologic/statistical information in the context of SNP selection following genome-wide linkage analyses that were promising strategies for reducing costs associated with genotyping while alleviating multiple testing concerns.…”
Section: Data Reductionmentioning
confidence: 99%
“…With respect to data reduction using biologic/statistical information, Huang et al [2007], Lam et al [2007], and Sinha and Luo [2007] evaluated methods for SNP selection following genome-wide linkage analyses. Huang et al [2007] performed expression QTL (eQTL) linkage analysis of expression data to determine how selecting significant SNPs in aggregate for follow-up studies differed from an approach that considered cis-and trans-acting SNPs separately.…”
Section: Data Reductionmentioning
confidence: 99%